Water filling of hydrophilic nanopores - De La Llave, E. (2010)
Molecular dynamics simulations of water in cylindrical hydrophilic pores with diameters of 1.5 and 3 nm were performed to explore the phase behavior and the nucleation dynamics of the confined fluid as a function of the percentage of volume filled f. The interactions of water with the pore wall were considered to be identical to the interactions between water molecules. At low water contents, all the water is adsorbed to the surface of the pore. A second phase consisting of a liquid plug appears at the onset filling for capillary condensation, fonset =27% and 34% for the narrow and wide pores, respectively. In agreement with experimental results for silica pores, the liquid phase appears close to the equilibrium filling feq in the 1.5 nm pore and under conditions of strong surface supersaturations for the 3 nm pore. After condensation, two phases, a liquid plug and a surface-adsorbed phase, coexist in equilibrium. Under conditions of phase coexistence, the water surface density Tcoex was found to be independent of the water content and the diameter of the pore. The value of Tcoex found in the simulations (∼3 nm-2) is in good agreement with experimental results for silica pores, suggesting that the interactions of water with silica and with itself are comparable. The surface-adsorbed phase at coexistence is a sparse monolayer with a structure dominated by small water clusters. We characterize the density and structure of the liquid and surface phases, the nucleation mechanism of the water plug, and the effect of surface hydrophilicity on the two-phase equilibrium and hysteresis. The results are discussed in light of experiments and previous simulations. © 2010 American Institute of Physics.